Model Kewirausahaan Pesantren Berbasis Nilai Islam untuk Kemandirian Ekonomi: Studi Kasus Pondok Modern Darussalam Gontor: An Islamic Values-Based Pesantren Entrepreneurship Model for Economic Independence: A Case Study of Pondok Modern Darussalam Gontor - Ahmad Tontowi Jauhari; Muh. Hasan Marwiji; Muhammad Syamsudin Nurfalah (Risalah Kharisma, 2026)
The challenge of achieving economic self-reliance for Islamic educational institutions underscores the importance of strengthening entrepreneurship in Islamic boarding schools. This study aims to analyze and formulate a model of entrepreneurship at Pondok Modern Darussalam Gontor in achieving economic self-reliance. This study employs a qualitative approach using a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis, and were subsequently analyzed using a descriptive-analytical approach. The results indicate that Pondok Modern Darussalam Gontor has developed various business units, such as a printing press, a student cooperative, a sharia-compliant microfinance institution (BMT), agriculture, livestock farming, and service providers, which are collaboratively managed by the leadership, teachers, alumni, and students. The management of these businesses integrates pesantren educational values, such as honesty, responsibility, and self-reliance. This study formulates a pesantren entrepreneurship model comprising three main components: collaborative management, business unit diversification, and the internalization of Islamic values as the foundation of economic self-reliance. This model contributes to enhancing the institution’s financial sustainability, strengthening students’ character, and contributing to the local economy. These findings indicate that an Islamic-values-based entrepreneurship model is effective in supporting the sustainable economic independence of Islamic educational institutions.